Terrestrial Species of Drouetiella (Cyanobacteria, Oculatellaceae) from the Russian Arctic and Subarctic Regions and Description of Drouetiella ramosa sp. nov. - Denis Davydov; Anna Vilnet; Irina Novakovskaya; Elena Patova (Diversity, 2023)
The strains of Drouetiella species (Cyanobacteria, Oculatellaceae) from a terrestrial biotope were isolated and characterized using an integrative approach including molecular, morphological, and ecological information. The specimens were collected from the Arctic and Subarctic areas of European Russia. Drouetiella species possess morphological plasticity and can be confused with similar species of Oculatellaceae or Leptolyngbyaceae. The 16S rRNA gene phylogeny supported the strong monophyly of the genus Drouetiella with the separation of four linages corresponding to three known species and one to new taxon. The 16S-23S ITS rRNA sequences of the analyzed Drouetiella strains differ in length and nucleotide composition, which has had an effect on the hypothetical secondary structures of the D1–D1′, Box-B, V2, and V3 helices. As a result of complex study of the genus Drouetiella, a new species—Drouetiella ramosa sp. nov.—is described from the Subarctic of European Russia.